BIODIVERSITY, SPATIAL AND ASSOCIATION PATTERNS OF NATURAL TREE SPECIES IN TROPICAL BROADLEAVED FOREST IN NORTHERN VIETNAM - Quoc Dung, Phan; Hong Hai, Nguyen (Journal of Forestry Science and Technology, 2018)
Ecological processes in forests can be studied via the spatial distribution of tree species. However, the distribution pattern of a species may be obscured by environmental heterogeneity. In order to answer these questions: What are the prevailing types of intraspecific spatial distributions and interspecific association patterns at tree species in a tropical rain forest? Which ecological processes could structure these patterns? The techniques of point pattern analysis were implemented on mapped two 1-ha forest plots in Ba Vi National Park, Cuc Phuong National Park. We analyzed (i) The effect of environmental heterogeneity on tree distributions; (ii) Intraspecific associations and (iii) Interspecific associations. Our analyses showed that: (i) Environmental conditions were homogeneous at all two plots. (ii) In two plots, almost dominant species were aggregated at various scales up to 50 m due to the limited distribution of each species while the rest was random distribution. (iii) Attraction and independence in two plots are remarkably higher than repulsion pattern of tree species. Overall, spatial aggregation of a species can be induced by limited seed dispersal or patchy habitat conditions while random distributions were effected by competitive relations or even human activities. The repulsive interactions between some tree species are explained by negative interactions of tree species.